STRATEGI PENERJEMAHAN ISTILAH BUDAYA SOSIAL DAN ORGANISASI SOSIAL: Penelitian Analisis Isi pada Penerjemahan Novel Bocchan Karya Natsume Soseki ke dalam Bahasa Indonesia - Hapsari, Eky Kusuma; Setiawati, Nia; Mutiara, Bella (Universitas Negeri Jakarta, 2020)
In Japanese not all words can be translated into Indonesian, especially a cultural word. Therefore, a translation strategy is needed to find a cultural equivalents. The purpose of this reserch is to know the social cultural and social organization and the translating strategies used in Natsume’s Bocchan novel. This is the descriptive qualitative reserch about content analysis. Based on the analysis of data, it is found seventy two cultural word that is (1) social culture is 25 data; and (2) organization cultural is 52 data. There are seven strategies used by translator, namely (1) twenty two words which translated using a loan word or loan word plus explanation; (2) twenty one words which translated paraphrase using a related word; (3) sixteen words which translated using cultural substitution; (4) ten words which translated using paraphrase using unrelated words; (5) four words which translated using a more general word; and (6) three words which translated using omission.